Enhance Student Discipline through Futsal Extracurriculars - Alfiah Nurjanah; Amanda Amanda; Adrian Surya; Ahmad Abdullah; Chandra Halim; Mochamad Whilky Rizkyanfi (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
Objectives. Physical education can be implemented through two distinct forms of learning activities: intracurricular and extracurricular. Extracurricular activities have the potential to indirectly enhance students' academic performance, interest, and talent. These activities serve as a forum for unlocking students' potential, developing their soft skills, and inculcating positive values, such as enhancing student discipline. The focus of this research is to measure the extent to which extracurricular futsal activities contribute to the enhancement of student discipline. Materials and methods. This study utilizes a research methodology known as Systematic Literature Review (SRL), which involves an extensive analysis of five scholarly articles published on Google Scholar within the past year. The purpose of this method is to compare and contrast the findings and conclusions of the selected articles, and to identify any gaps or inconsistencies in the existing research. By employing SRL, this study aims to provide a comprehensive and rigorous analysis of the current literature on the topic at hand, and to generate new insights and recommendations for future research. Results. Based on the analysis of various academic sources, it has been established that engaging in Futsal extracurricular activities can prove to be beneficial in enhancing student discipline. The outcomes of the literature review suggest that students who participate in Futsal activities tend to exhibit better self-control, time management skills and have a more structured routine, which ultimately leads to a positive impact on their academic performance. Conclusion. According to empirical research, there exists a significant relationship between the degree of student discipline and their academic achievement. An increase in discipline has been found to lead to improved academic performance. This finding has important implications for educational institutions seeking to enhance the learning outcomes of their students.